Phenotypic Heterogeneity of Post-lingual and/or Milder Hearing Loss for the Patients With the GJB2 c.235delC Homozygous Mutation - Wang, Hongyang; Gao, Yun; Guan, Jing; Lan, Lan; Yang, Ju; Xiong, Wenping; Zhao, Cui; Xie, Linyi; Yu, Lan; Wang, Dayong; Wang, Qiuju (Frontiers in Cell and Developmental Biology, 2021)
Objective: To report the phenotypic heterogeneity of GJB2 c.235delC homozygotes associated with post-lingual and/or milder hearing loss, and explore the possible mechanism of these unconditional phenotypes. Methods: Mutation screening of GJB2 was performed on all ascertained members from Family 1006983 and three sporadic patients by polymerase chain reaction (PCR) amplification and Sanger sequencing. Next generation sequencing (NGS) was successively performed on some of the affected members and normal controls from Family 1006983 to explore additional possible genetic codes. Reverse transcriptase–quantitative PCR was conducted to test the expression of Connexin30. Results: We identified a Chinese autosomal recessive hearing loss family with the GJB2 c.235delC homozygous mutation, affected members from which had post-lingual moderate to profound hearing impairment, and three sporadic patients with post-lingual moderate hearing impairment, instead of congenital profound hearing loss. NGS showed no other particular variants. Overexpression of Connexin30 in some of these cases was verified. Conclusion: Post-lingual and/or moderate hearing impairment phenotypes of GJB2 c.235delC homozygotes are not the most common phenotype, revealing the heterogeneity of GJB2 pathogenic mutations. To determine the possible mechanism that rescues part of the hearing or postpones onset age of these cases, more cases are required to confirm both Connexin30 overexpression and the existence of modifier genes.